Operational distribution of the train traffic volume on the sections of railway operating domain - Mozolevich, G. Ya. (Science and Transport Progress, 2013)
Purpose. The task of the operational distribution of train traffic volume on the sections of operating domain is the optimization one. It is solved in the operational conditions by the dispatch station. The article sets the problem of formalizing and finding the new ways to solve this urgent problem. Methodology. A new approach to solving the problem of operational distribution of train traffic volume on the sections of the rail network with a choice of routes for all train traffics was proposed. Findings. A study of possible routes for the train traffic handle on the operating domain used for mass freight transportations between Krivyi Rih and Donbas was carried out. The use of the proposed method allowed us to obtain a rational distribution of trains on the rail network sections. Originality. The method of train traffic volume distribution in the network under operational conditions was improved. The method, as opposed to the current one allows one to select the route of separate units handle (according to the criteria of the weighted average cost for 1 ton of cargo). Practical value. The use of the proposed technology of the operational distribution of train traffic volume will increase the efficiency of the railways in general and ensure the competitiveness of rail transportations. The methodology implementation involves the use of railway dispatch station for the automated workplaces with appropriate informational support.